2010
DOI: 10.1149/1.3478569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bulky Copolymers on Ion Transport in an Anhydrous Proton-Conducting Electrolyte

Abstract: Anhydrous proton-conducting electrolytes composed of a mixture of MePEG 7 SO 3 H ͓where PEG is poly͑ethylene glycol͔͒ acid and a sol-gel-based MePEG 3 copolymer were prepared. These copolymers were prepared by mixing the MePEG 3 ͑CH 2 ͒ 3 Si͑OCH 2 CH 3 ͒ 3 monomer and different bulky comonomers: phenyltriethoxysilane, diphenyldimethoxysilane, and isobutyltrimethoxysilane. The MePEG 3 copolymers showed smaller volume fractions of PEG and nearly the same fractional free volume as the parent MePEG 3 polymer. End-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 42 publications
(100 reference statements)
0
22
0
Order By: Relevance
“…In general, the MePPG 3 polymer has greater FFV than the MePEG 7 polymer, and the copolymerization of MePPG 3 with the MePEG 7 polymer leads to copolymers with greater FFV as compared to the MePEG 7 polymer. While the differences in FFV seen in Table appear to be small, we have found that these small differences in FFV can have a large effect on the ionic conductivity. , …”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In general, the MePPG 3 polymer has greater FFV than the MePEG 7 polymer, and the copolymerization of MePPG 3 with the MePEG 7 polymer leads to copolymers with greater FFV as compared to the MePEG 7 polymer. While the differences in FFV seen in Table appear to be small, we have found that these small differences in FFV can have a large effect on the ionic conductivity. , …”
Section: Resultsmentioning
confidence: 66%
“… a The effective MW for copolymers represents the MW of one “repeat unit” of the polymer. One repeat unit of MePEG 7 polymer is defined as MePEG 7 OCH 2 CH 2 CH 2 SiO 3/2 . b V m for polymers and copolymers represents the weighted V m calculated using the effective MW. c V w for polymers and copolymers represents the weighted V w calculated by the Bondi group contribution method. d Fractional free volume (FFV) is calculated according to eq . e The calculation of the volume fraction of ether ( V f,ether ) has been reported. ,, f The 75:25 ratio indicates that this copolymer is 75% mole fraction MePEG 7 polymer and 25% mole fraction MePPG 3 polymer (Table S1, Supporting Information). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycol (PEG) (also known as poly­(ethylene oxide) (PEO) in its long chain form) is a water-soluble polymer that has been widely studied for its interesting properties in aqueous environments. These properties include interactions of its ethylene oxide (EO) chains in aqueous solutions, the ability to adsorb on surfaces and interfaces, and proton conductivity in polymer electrolytes. The interaction of water with the PEG chain backbone has been widely studied to date, both by experiment ,, and simulation , due to the interesting ability of PEG to form bridged hydrogen bonds (HBs) from EO monomer units to water molecules to other EO monomer units within the same chain . These properties give PEG a wide variety of applications such as biphasic (two-phase) liquid–liquid catalysis, electrochemical energy conversion as a proton exchange membrane additive, , and in drug delivery via modification of therapeutic molecules (known as PEGylation). …”
Section: Introductionmentioning
confidence: 99%
“…6−18 The interaction of water with the PEG chain backbone has been widely studied to date, both by experiment 2,3,19 and simulation 4,20−26 due to the interesting ability of PEG to form bridged hydrogen bonds (HBs) from EO monomer units to water molecules to other EO monomer units within the same chain. 4 These properties give PEG a wide variety of applications such as biphasic (twophase) liquid−liquid catalysis, 27 electrochemical energy conversion as a proton exchange membrane additive, [8][9][10][11][12][13][14]28 and in drug delivery via modification of therapeutic molecules (known as PEGylation). 29−31 The conductivity of various ions with PEG in aqueous solution has also been of research interest in past years.…”
Section: Introductionmentioning
confidence: 99%